Tolerance in the Perspective of Surah Al-Kafirun - Azhar (International Journal of Educational and Life Sciences, 2024)
This research discusses focusing on Surah Al-Kafirun and hadis which are relevant in the context of religious tolerance. This surah (Al-Kafirun) was revealed in response to the polytheists' offer to the Prophet Muhammad Saw to alternately worship Allah and their gods, highlighting the importance of the principle of oneness in Islam. Currently, there is disharmony between non-Islamic and Muslim communities, particularly regarding the term "kafir," which is often perceived as discrediting those outside of Islam. Several of Mufassir, such as Al-Tabari, state that these verses were addressed to the leaders of the polytheists, while Al-Razi emphasizes that the Prophet did not permit his followers to commit disbelief, as he was sent to guide his people towards goodness. This research is a library study that examines verses and hadis as well as literature from various mufassir that are relevant in the Quran and hadis, particularly in the context of Surah Al-Kafirun. The author argues that the term "kafir," meaning "closed heart," is more appropriate than "non-Muslim," which translates to "not safe." Through this analysis, the author hopes to demonstrate that although the term carries negative connotations, every closed heart has the potential to open through Allah's guidance. This creates hope for building better tolerance among religious communities, promoting dialogue and deeper understanding.